Identification of candidate genes of QTLs for seed weight in Brassica napus through comparative mapping among Arabidopsis and Brassica species - Cai, Guangqin (BioMed Central, 2012)
BACKGROUND: Map-based cloning of quantitative trait loci (QTLs) in polyploidy crop species remains a challenge due to the complexity of their genome structures. QTLs for seed weight in B. napus have been identified, but information on candidate genes for identified QTLs of this important trait is still rare. RESULTS: In this study, a whole genome genetic linkage map for B. napus was constructed using simple sequence repeat (SSR) markers that covered a genetic distance of 2,126.4 cM with an average distance of 5.36 cM between markers. A procedure was developed to establish colinearity of SSR loci on B. napus with its two progenitor diploid species B. rapa and B. oleracea through extensive bioinformatics analysis. With the aid of B. rapa and B. oleracea genome sequences, the 421 homologous colinear loci deduced from the SSR loci of B. napus were shown to correspond to 398 homologous loci in Arabidopsis thaliana. Through comparative mapping of Arabidopsis and the three Brassica species, 227 homologous genes for seed size/weight were mapped on the B. napus genetic map, establishing the genetic bases for the important agronomic trait in this amphidiploid species. Furthermore, 12 candidate genes underlying 8 QTLs for seed weight were identified, and a gene-specific marker for BnAP2 was developed through molecular cloning using the seed weight/size gene distribution map in B. napus. CONCLUSIONS: Our study showed that it is feasible to identify candidate genes of QTLs using a SSR-based B. napus genetic map through comparative mapping among Arabidopsis and B. napus and its two progenitor species B. rapa and B. oleracea. Identification of candidate genes for seed weight in amphidiploid B. napus will accelerate the process of isolating the mapped QTLs for this important trait, and this approach may be useful for QTL identification of other traits of agronomic significance.